This is a tutorial on completing the square of quadratic expressions.

The idea of completing the square stems from the following result x^{2} + bx = (x + b/2)^{2} - (b/2) ^{2}

Exercise:Complete the square for the follwoing quadratic expressions

Solutions to Exercises Above : A) x^{2} + 4x = (x + 2)^{2} - 4 B) x^{2} + 6x - 3 = (x + 3)^{2} - 12 C) -x^{2} - 4x + 2 = -(x + 2)^{2} + 6 D) -2x^{2} - 5x - 5 = -2(x + 5/4)^{2} - 15/8 More references and links on the quadratic functions in this website.